Dabrafenib plus trametinib in patients with BRAFV600-mutant melanoma brain metastases (COMBI-MB): a multicentre, multicohort, open-label, phase 2 trial - Davies, Michael A; Saiag, Philippe; Robert, Caroline; Grob, Jean-Jacques; Flaherty, Keith T; Arance, Ana; Chiarion-Sileni, Vanna; Thomas, Luc; Lesimple, Thierry; Mortier, Laurent; Moschos, Stergios J; Hogg, David; et al. (The lancet oncology, 2017)
Dabrafenib plus trametinib improves clinical outcomes in BRAFV600-mutant metastatic melanoma without brain metastases; however, the activity of dabrafenib plus trametinib has not been studied in active melanoma brain metastases. Here, we report results from the phase 2 COMBI-MB trial. Our aim was to build on the current body of evidence of targeted therapy in melanoma brain metastases through an evaluation of dabrafenib plus trametinib in patients with BRAFV600-mutant melanoma brain metastases. This ongoing, multicentre, multicohort, open-label, phase 2 study evaluated oral dabrafenib (150 mg twice per day) plus oral trametinib (2 mg once per day) in four patient cohorts with melanoma brain metastases enrolled from 32 hospitals and institutions in Europe, North America, and Australia: (A) BRAFV600E-positive, asymptomatic melanoma brain metastases, with no previous local brain therapy, and an Eastern Cooperative Oncology Group (ECOG) performance status of 0 or 1; (B) BRAFV600E-positive, asymptomatic melanoma brain metastases, with previous local brain therapy, and an ECOG performance status of 0 or 1; (C) BRAFV600D/K/R-positive, asymptomatic melanoma brain metastases, with or without previous local brain therapy, and an ECOG performance status of 0 or 1; and (D) BRAFV600D/E/K/R-positive, symptomatic melanoma brain metastases, with or without previous local brain therapy, and an ECOG performance status of 0, 1, or 2. The primary endpoint was investigator-assessed intracranial response in cohort A in the all-treated-patients population. Secondary endpoints included intracranial response in cohorts B, C, and D. This study is registered with ClinicalTrials.gov, number NCT02039947. Between Feb 28, 2014, and Aug 5, 2016, 125 patients were enrolled in the study: 76 patients in cohort A; 16 patients in cohort B; 16 patients in cohort C; and 17 patients in cohort D. At the data cutoff (Nov 28, 2016) after a median follow-up of 8·5 months (IQR 5·5–14·0), 44 (58%; 95% CI 46–69) of 76 patients in cohort A achieved an intracranial response. Intracranial response by investigator assessment was also achieved in nine (56%; 95% CI 30–80) of 16 patients in cohort B, seven (44%; 20–70) of 16 patients in cohort C, and ten (59%; 33–82) of 17 patients in cohort D. The most common serious adverse events related to study treatment were pyrexia for dabrafenib (eight [6%] of 125 patients) and decreased ejection fraction (five [4%]) for trametinib. The most common grade 3 or worse adverse events, regardless of study drug relationship, were pyrexia (four [3%] of 125) and headache (three [2%]). Dabrafenib plus trametinib was active with a manageable safety profile in this melanoma population that was consistent with previous dabrafenib plus trametinib studies in patients with BRAFV600-mutant melanoma without brain metastases, but the median duration of response was relatively short. These results provide evidence of clinical benefit with dabrafenib plus trametinib and support the need for additional research to further improve outcomes in patients with melanoma brain metastases. Novartis.